Intention In Buying Video- On-Demand Subscription Services - Sabilla, Sania Aurora; Dirgantara, I Made Bayu (LifeSciFi, 2025)
Nowadays subscription video-on-demand seems to become a solution to entertainment access in the form of video such as movies and series. Through the subscription video-on-demand service, consumers can control what they want to watch, which can be accessed anytime and anywhere if the electronic device is connected to the internet. Seeing many internet users in Indonesia, making subscription video-on-demand service have great potential to develop in Indonesia. In addition, the development of the SVOD industry is accompanied by a high level of competitiveness in it. So, it needs a strategy to expand the market by having more customers for business continuity and growth of the subscription video-on-demand platform. Therefore, it is important to find out the factors that influence the intention in purchasing subscription video-on-demand. The research was conducted using a sample of 152 respondents with the criteria of being domiciled in Semarang City and knowing about video on demand subscription services. Data were obtained from questionnaires which were then processed and analysed using Structural Equation Modelling (SEM) as analytical methods and AMOS as a data processing tool. The author found that perceived usefulness, perceived enjoyment, social value, perceived ease of use, and perceived price have a significant effect on the purchase intention of subscription video-on-demand.